PENGEMBANGAN APLIKASI KELAS IBU HAMIL BERBASIS ANDROID MENGGUNAKAN FRAMEWORK FLUTTER - Aristoteles, Aristoteles; Yandika, Raymond Faraz; Sudarmi, Sudarmi; Muhaqiqin, Muhaqiqin; Irawati, Anie Rose (Lambung Mangkurat University, 2023)
Kelas Ibu Hamil (KIH) Resiko Tinggi Kehamilan (Restikol) is a means for learning about health, especially related to pregnancy, in the form of face-to-face and in groups that aim of improving the knowledge and skills of pregnant women. KIH is actively running in Lampung Provinsi particularly in Lampung Selatan Regency. There are 27 Puskesmas and 297 groups. Health workers who are directly involved in the implementation of the KIH are 1513 with the highest number of health workers 652 midwives. This KIH activity is difficult to do, especially during a pandemic, with limited face-to-face activities, other means are needed to support KIH. By utilizing a smartphone-based application, KIH activities can be continued. The application is built by the SCRUM method and uses the flutter framework.